(untitled) (Sciences & Technology. A, exactes sciences, 2005)
The photoconductivity of ZnO thin films prepared by spray pyrolysis of the zinc dihydrated were studied. The electrical, optical behaviors and structural spectra show an important effect of substrate temperature Ts and deposition time td. Under illumination, the conductivity of asgrown sample increased due to desorption of oxygen. A small photoconductivity is representative of the electrical behavior of a quasi intrinsic material. By following cessation of illumination, we remarked a saturation of decay photoconductivity, this can be attributed to traps which captures carriers